Caregivers' knowledge and attitudes about childhood diarrhea among refugee and host communities in Gambella Region, Ethiopia - Getachew Kabew Mekonnen; Bezatu Mengistie; Geremew Sahilu; Worku Mulat; Helmut Kloos (BMC, 2018)
Abstract Background Maternal knowledge, attitudes, and practices related to hygiene, breastfeeding, sanitary food preparation, and appropriate weaning practices are potentially important determinants in the occurrence of diarrhea in children. However, few studies have been carried out about the knowledge and attitudes about childhood diarrhea among parents in refugee camps and host communities. Objective This study aims at assessing the caregivers' knowledge and attitudes regarding acute diarrhea in under-five children among refugee and host communities in Gambella Region, Ethiopia. Methodology This cross-sectional study, employing multistage sampling, was carried out from September to December 2016. Data was collected by a questionnaire-based interview, and 1667 caregivers were included in this study. A composite knowledge score was calculated, and a five-point Likert type of attitude scale was developed to assess the attitudes of the caregivers towards childhood diarrhea. Appropriate descriptive statistics and logistic regression models were used. Odds ratios (ORs) are presented with their 95% confidence intervals (CIs), and all analyses were performed at the 5% significance level (p < 0.05). Result The study indicates that 633 (28.0%) of the caregivers had poor knowledge, while 393 (23.6%) of them had unfavorable attitudes towards childhood diarrhea. Knowledge of the caregivers was significantly associated with formal education (AOR, 1.3; 95% CI, 1.03-1.5) and health information obtained from a health care institution (AOR, 1.8; 95% CI, 1.28-2.3). Caregivers' knowledge is a single predictor of their attitude (p < 0.001), and Pearson's correlation coefficient revealed that there was a significant positive correlation (r = 0.2, p < 0.001) between knowledge and attitude scores. Conclusion The study indicates that significant numbers of caregivers had inadequate knowledge and unfavorable attitudes about diarrhea in under-five children. Designing and implementing an inclusive health education intervention focusing on uneducated child caregivers may be beneficial for improving knowledge and attitudes towards reducing the incidence of acute childhood diarrhea in the region.